Precision of C-reactive protein in the diagnosis of acute appendicitis - Melody Omraninava; Shaghayegh Javan; Ghahraman Mahmodi (Shahid Beheshti University of Medical Sciences, 2022)
Background: Appendicitis is known as inflammation in the appendix, and its treatment is merely through surgery. There is mistaken diagnosis according to clinical presentations. C-reactive protein is an annular pentameric protein found in blood plasma, whose circulating concentrations rise in response to inflammation. It is an acute-phase protein of hepatic origin. Therefore, the aim of this study was to evaluate the diagnostic effect of C-Reactive Protein (CRP) in the diagnosis of acute appendicitis in patients referring to Valiasr Hospital in Qaemshahr city, Iran in 2017-2018. Methods: This study was a diagnostic study and blood samples were collected from patients with acute abdomen pain with suspected appendicitis in Qaemshahr Valiasr Hospital. Then CRP results were compared with pathological results as golden standard; then sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of this test were determined based on standardized test (pathologic result). Results: The sensitivity and specificity of CRP test in diagnosis of acute appendicitis were 71.42% and 60.58%, respectively. In addition, PPV and NPV were 88.88% and 42.85%, respectively. Conclusion: According to the results of this study, CRP can be considered as one of the predictive tests of acute appendicitis. Evaluation of CRP levels, alongside with other diagnostic approaches, can be used as an adjunctive diagnostic method in the diagnosis of acute appendicitis.